x dx 1 2x dx 1 d(7+x²) 1
∫ = ∫ = ∫ = ln(7+x²)+C
7+x² 2 7+x² 2 7+x² 2
[1/2 *ln(7+x²)+C ]¹= 1/2*[ 2x /(7+x²)+0]= x /(7+x²)
x+18 (x-2)+20 1 2(x-2) dx
2) ∫dx=∫ dx= ∫ dx+20 ∫ =
x²-4x-12 (x-2)²-16 2 (x-2)²-16 (x-2)²-16
1 1 | x-2-4 | 1 5 | x-6 |
= *ln|(x-2)²-16|+20 * *ln || +C= *ln |x²-4x-12|+*ln || +C
2 2*8 | x-2+4 | 2 4 | x+2 |
3) ∫(3-x) cosx dx=[ u=3-x , du=-dx , dv=cosx dx , v=sinx ] =(3-x)sinx+∫ sinx dx=
=(3-x)sinx-cosx+C
[(3-x)sinx-cosx]¹= -sinx+(3-x)cosx+sinx +0=(3-x)cosx
x dx 1 2x dx 1 d(7+x²) 1
∫ = ∫ = ∫ = ln(7+x²)+C
7+x² 2 7+x² 2 7+x² 2
[1/2 *ln(7+x²)+C ]¹= 1/2*[ 2x /(7+x²)+0]= x /(7+x²)
x+18 (x-2)+20 1 2(x-2) dx
2) ∫dx=∫ dx= ∫ dx+20 ∫ =
x²-4x-12 (x-2)²-16 2 (x-2)²-16 (x-2)²-16
1 1 | x-2-4 | 1 5 | x-6 |
= *ln|(x-2)²-16|+20 * *ln || +C= *ln |x²-4x-12|+*ln || +C
2 2*8 | x-2+4 | 2 4 | x+2 |
3) ∫(3-x) cosx dx=[ u=3-x , du=-dx , dv=cosx dx , v=sinx ] =(3-x)sinx+∫ sinx dx=
=(3-x)sinx-cosx+C
[(3-x)sinx-cosx]¹= -sinx+(3-x)cosx+sinx +0=(3-x)cosx
2)0,4(х-9)-0,3(х+2)=0,7
0,4х-3,6-0,3х-0,6=0,7
0,4х-0,3х=0,7+3,6+0,6
0,1х=4,9
Х=4,9:0,1
Х=49
ответ:49
...